Application of the digital literacy module and development of digital competences in teachers - Agustín Rufino Rojas Flores (2018)
Nowadays it is not enough to be well informed, we need to be able to reach the levels of competencies necessary to develop ourselves in work and in society. In the city of Huánuco, teachers are slowly entering into the use of computer resources within their pedagogical activities, and the Ministry of Education, for its part, implements educational resources with computer resources. There are students who live with computer media, with whom the teacher has to share the teaching - learning process. In this reality, the question is posed: Will the application of the Digital Literacy module improve the digital skills of teachers, Huánuco, 2016? having as objective to determine if when applying the module Digital Literacy improves the digital competences in the teachers. The quasi-experimental design of a pre-test and post-test with a single group is assumed, with 22 teachers as sample. The module was applied in a period of 5 months and the McNemar test was applied to contrast hypotheses, obtaining that the application of the Digital Literacy module improves digital skills in teachers (significant development of information management, communication and problem solving) and not in content creation and security.